Fluorogenic 7-azidocoumarin and 3/4-azidophthalimide derivatives as indicators of reductase activity in microorganisms. Issue 16 (15th August 2019) - Chalansonnet, Valerie; Lowe, John; Orenga, Sylvain; Perry, John D.; Robinson, Shaun N.; Stanforth, Stephen P.; Sykes, Hannah E.; Truong, Thang V.
Graphical abstract: Abstract: A series of fluorogenic heterocyclic azides were prepared and assessed as reductase substrates across a selection of Gram-negative and Gram-positive microorganisms. The majority of these azides showed similar activity profiles to nitroreductase substrates. Microorganisms that do not produce hydrogen sulfide reduced the azides, indicating reductase activity was not linked to hydrogen sulfide production.